Investigation on Stand-Alone Solar System for rural electrification / Khairi A.M. Elrmali - Khairi A. M., Elrmali (2018)
Stand-alone photovoltaic systems along with a battery storage system play a significant role in providing electricity to remote off-grid communities. The main objective of this research project is to understand the design and operation principles of a stand-alone PV system. The procedures for the design and sizing of a small stand-alone PV electricity system suitable for small off grid household has been reviewed. Subsequently, a manual sizing guideline is implemented in Excel sheet and compared with commercial software PVsyst. To further understand the operation of the stand-alone PV system, simulation model has been developed in MATLAB/SIMULINK environment. Operations of the stand-alone PV system with PWM charge controller were studied under varying conditions. From the simulation, it was found that the matching of PV and battery voltage is important to ensure good energy yield in the system. Overall the project has provided good understanding on the various components and their operation concepts in stand-alone PV system.